TEORI BELAJAR HUMANISME DAN IMPLIKASINYA DALAM PEMBELAJARAN BAHASA ARAB - Abdullah Syahid Robbani; Ahmad Muzayyan Haqqy (Tarling : Journal of Language Education, 2021)
Learning is a process/effort/activity carried out by the individual to obtain a change in personality or behavior. The current learning process seems like a teacher filling an empty glass, or like a mother feeding her child food. The theory of learning humanism arises with the aim that learners can become responsible individuals, attentive to their environment, and have emotional and spiritual maturity. This article is a literature study and uses qualitative descriptive methods and tries to examine the theory of humanism learning and its implications in Arabic language learning. The results showed that humanism learning theory can be applied by formulating clear learning objectives, working on the active participation of learners, encouraging learners to think critically and dare to express opinions, and how a teacher in the learning process tries to understand the learner's way of thinking and give them an opportunity. And with the implementation of the theory of humanism learning, students are expected to be individuals who have good academic ability and morals so that in the future will reduce the problems and social deviations that exist; able to develop their abilities both in terms of cognitive, affective, and psychomotor as well as being responsible individuals and having emotional maturity and being able to actualize themselves; students become more motivated to acquire new skills, skills and wider knowledge in Arabic language learning.